2023
DOI: 10.37201/req/014.2023
|View full text |Cite
|
Sign up to set email alerts
|

High macrolides and fluoroquinolones resistance rate in Mycoplasma genitalium in southern Tenerife

Abstract: Introduction. Mycoplasma genitalium (MG) is a recognized sexually transmitted pathogen. Increasing resistance to main lines of treatment (macrolides and quinolones) justifies a genetic study of mutations to improve cure rates. Material and methods. A total of 8,508 samples from April 2018 to July 2022 were processed using AllplexTM STI Essential Assay. In MG positive cases 23S rRNA V domain, gyrA and parC genes were studied. Mutations detected were checked to assess their clinical significance and medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
1
4
1
Order By: Relevance
“…The main mutation detected in Azi-R-MG in the present study has been A2059G (55/95, 57.9%), which was the most frequent in the fore-mentioned report (55.6%). Our results are similar to those performed in other Spanish areas: a study performed in Tenerife (Canary Islands, Spain) found that 17 out of 28 samples have the A2059G mutation [ 11 ], and in a report from the south of Spain, the same mutation was described in the 50% of Azi-R-MG samples [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The main mutation detected in Azi-R-MG in the present study has been A2059G (55/95, 57.9%), which was the most frequent in the fore-mentioned report (55.6%). Our results are similar to those performed in other Spanish areas: a study performed in Tenerife (Canary Islands, Spain) found that 17 out of 28 samples have the A2059G mutation [ 11 ], and in a report from the south of Spain, the same mutation was described in the 50% of Azi-R-MG samples [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…The main parC mutation detected was G248T (19/26), which agrees with previously reports [ 3 , 7 , 10 ]. In our study, we only evaluated the parC gene, although some studies reported that resistance to moxifloxacin is also due to mutations in gyrA gene [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations